Pengaruh Pengembangan Karir Terhadap Produktivitas Kerja Pada Dinas Kelautan, Pertanian Kota Gorontalo - Zaurah Utiarahman; Irina Popoi; Abdulrahim Maruwae (Journal of Economic and Business Education, 2023)
This study aims to determine the effect of career development on employee’s work productivity at the Department of Marine Affairs, Fisheries, and Agriculture of Gorontalo City. This study applied a quantitative approach. Data were collected through observation, documentation, and questionnaire. The samples consisted of 58 respondents. Data were analysed descriptively using validity test, reliability test, normality test, heteroscedasticity test, and simple linear regression test. The results of this study revealed that career development has an effect on employee’s work productivity at the Department of Marine Affairs, Fisheries, and Agriculture of Gorontalo City. The R-Square value obtained 17.5%, indicating that the variability of work productivity in the Department of Marine Affairs, Fisheries, and Agriculture of Gorontalo City can be explained by career development. Meanwhile, the remaining 82.5% is influenced by other variables that are not examined in this study.